Assessment of stress/strain in dental implants and abutments of alternative materials compared to conventional titanium alloy—3D non-linear finite element analysis. Issue 8 (10th June 2020) - Tretto, Pedro Henrique Wentz; dos Santos, Mateus Bertolini Fernandes; Spazzin, Aloisio Oro; Pereira, Gabriel Kalil Rocha; Bacchi, Atais
Abstract: The aim of this study was to assess the stress/strain in dental implant/abutments with alternative materials, in implants with different microgeometry, through finite element analysis (FEA). Three-dimensional models were created to simulate the clinical situation of replacement of a maxillary central incisor with implants, in a type III bone, with a provisional single crown, loaded with 100 N in a perpendicular direction. The FEA parameters studied were: implant materials—titanium, porous titanium, titanium-zirconia, zirconia, reinforced fiberglass composite (RFC), and polyetheretherketone (PEEK); and abutment materials—titanium, zirconia, RFC, and PEEK; implant macrogeometry—tapered of trapezoidal threads (TTT) and cylindrical of triangular threads (CTT) (ø4.3 mm × 11 mm). Microstrain, von Mises, shear, and maximum and minimum principal stresses in the structures and in peri-implant bone were compared. There was increased stress and strain in peri-implant bone tissue caused by implants of materials with lower elastic modulus (mainly for PEEK and RFC). They also presented higher concentration of stresses in the implant itself (especially RFC). Zirconia implants led to lower stress and strains in peri-implant bone tissue. Less rigid abutments (RFC and PEEK) associated with titanium implants led to higher stress in the implant and in peri-implant bone tissue. The TTT macrogeometry showed a higher stress concentration in the implant and peri-implant bone tissue. The stress/strain in peri-implant bone tissue and implant structures were affected by the material used, where reduced values were caused by stiffer materials. Lower stress/strain values were obtained with cylindrical implants of triangular treads.